Pengaruh Signifikan Pada Profesional Guru Terhadap Prestasi Belajar Siswa Pada Mata Pelajaran Ekonomi Kelas VIII SMPN 2 Jerowaru - Muhamad Zaril Gapari (Pendidikan Al-Gafari, 2023)
Professional teachers are those who are qualified, competent, and teachers who desire to bring about learning achievement and can influence the teaching and learning process of students which will result in good student learning achievement. Teachers or educators are true leaders, wise guides and directors, figures, and leaders of the ummah. Teachers are professional educators with the main task of educating, teaching, guiding, directing, training, assessing, and evaluating. Teachers are professional educators with the main task of educating, teaching, guiding, directing, training, assessing, and evaluating students in primary and secondary education. as well as students in primary and secondary education. This study aims to determine the effect of professional teachers on learning achievement in economic subjects in class Kelas VIII SMPN 2 Jerowaru. The type of research used in this research is descriptive research. This study uses a quantitative approach. The population in this study were all students of class VIII SMPN 2 Jerowaru and the sample was 22 students of class VIII. The data collection technique used was a questionnaire. The data analysis technique used is the